2000
DOI: 10.3354/meps194269
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic ciliates in the oligotrophic Eastern Mediterranean:vertical, spatial distribution and mixotrophy

Abstract: Abundance, biomass, vertical distribution, species composition and rnivotrophy of planktonic ciliates were investigated during March 1997 in the oligotrophic Eastern Mediterranean. Six depth layers were sampled in the euphotic zone (0 to 100 m) at 7 stations in the North and 4 in the South Aegean Sea, resulting in a total of 66 samples and 82 ciliate species. Abundance was in general very low (0 to 780 cells I-') except from specific stations in the North Aegean stations (20 to 2040 cells I-'), influenced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
4
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 36 publications
9
55
4
5
Order By: Relevance
“…For example, in the Catalan Sea in June, the highest values of about 850 cells l −1 were found at the DCM, whereas in the Ligurian Sea in May average surface layer values (5-50 m) were ∼3.3×10 3 cells l −1 with a maximum of ∼10 4 cells l −1 (Peréz et al, 1997). These high values contrast with those for the Aegean Sea, where ciliate abundance was always lower than 5×10 2 cells l −1 (Pitta and Giannakourou, 2000). Pitta et al (2001) reported a 2-fold decrease in ciliates concentration from west to east.…”
Section: Ciliatescontrasting
confidence: 41%
See 1 more Smart Citation
“…For example, in the Catalan Sea in June, the highest values of about 850 cells l −1 were found at the DCM, whereas in the Ligurian Sea in May average surface layer values (5-50 m) were ∼3.3×10 3 cells l −1 with a maximum of ∼10 4 cells l −1 (Peréz et al, 1997). These high values contrast with those for the Aegean Sea, where ciliate abundance was always lower than 5×10 2 cells l −1 (Pitta and Giannakourou, 2000). Pitta et al (2001) reported a 2-fold decrease in ciliates concentration from west to east.…”
Section: Ciliatescontrasting
confidence: 41%
“…In the Ligurian Sea, nano-and micro-mixotrophic ciliate contribution to total oligotrich biomass and abundance ranged from 31 to 41% and from 42 to 54%, respectively and they were mainly located at the level of the DCM (Peréz et al, 1997). In a comparative study of the ciliates in the North and the South Aegean Sea, mixotrophs contributed to total abundance from 17 to 24% in the South and from 21 to 54% in the North, and in terms of integrated biomass the values varied from 13 to 27% and from 18 to 62% in the South and North, respectively (Pitta and Giannakourou, 2000). Mixotrophs were dominated by distinct morphotypes as well.…”
Section: Ciliatesmentioning
confidence: 99%
“…Temporal and spatial events that see mixotrophs as important members of the plankton include survival and growth of larval fish in temperate waters (de Figueiredo et al, 2007;Montagnes et al, 2010), and production in the oligotrophic systems that cover most of the oceans (Pitta and Giannakourou, 2000;Unrein et al, 2007;Zubkov and Tarran, 2008;Stukel et al, 2011;Hartmann et al, 2012). The interplay between nutrient stoichiometry, ecosystem maturity and success of mixotrophy also helps to explain why eutrophication is often associated with mixotrophic HABs and EDABs (Burkholder et al, 2008;Glibert and Burkholder, 2011;Burkholder and Glibert, 2013).…”
Section: Climate Change Eutrophication and Mixotrophymentioning
confidence: 99%
“…Indeed, there is increasing evidence that in most aquatic systems the majority of protists are mixotrophs engaging in varying proportions of phototrophy and phagotrophy (Sanders, 1991b;Burkholder et al, 2008;Raven et al, 2009;Stoecker et al, 2009;Jeong et al, 2010;Lindehoff et al, 2010;Hansen, 2011;Johnson, 2011). Often the marine ecosystems are heavily dependent upon the activity of these mixotrophic protists (Pitta and Giannakourou, 2000;Unrein et al, 2007;Zubkov and Tarran, 2008;Hartmann et al, 2012;Sanders and Gast, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation